The effect of Aqueous Olive Leaves Extract on the Pancreatic Islets of Streptozotocin Induced Diabetes Mellitus in mice - Al-Badri, Sanarya T.; Al-Ani, Imad Matloub Dally; Al-Jashamy, Karim A. (Department of Anatomy, National University of Singapore, 2011)
The objectives of this study were to investigate the effects of the aqueous crude extract of Olea europaea on serum glucose level and histopathological changes in islets of Langerhans in an induced-diabetic mellitus in mice. The experimental recommended 60 male mice were divided into three groups contained 20 mice each. The fi rst group was the control and they were given normal saline pH 7.0. The second group was intraperitoneally injected by a dose of 100mg/Kg of STZ and 10% glucose instead of normal drinking water over the 24 hours followed the treatment. The third group was injected intraperitoneally with 100mg/kg STZ and orally given 0.33g/ Kg aqueous extract of olive leaves everyday for four weeks. Blood specimens were collected, and the serum separated and stored at 4OC until it is used. The animals were dissected and the pancreatic tissues were obtained, the tissue specimens were fi xed in the Boun’s solution for 24 hr, and processed for histological studies. There was a signifi cant increase in blood glucose level of the STZ- diabetic mice by the fi rst week of injection with STZ in comparison with control group. A signifi cant decrease in blood glucose level occurred in the STZ-diabetic group treated with Olea europaea aqueous extract. Islets of langerhans are hypertrophied in the STZ-diabetic group and this hypertrophy showed a signifi cant increased in the average of islets size at the last week, while the treatment with Olea europaea aqueous extract showed a reduction of the islet size compared with the islets of the STZ –diabetic Mice